Zinc in cereal grains: Concentration, distribution, speciation, bioavailability, and barriers to transport from roots to grains in wheat. Issue 28 (3rd October 2022) - Aiqing, Zhao; Zhang, Liansheng; Ning, Peng; Chen, Qin; Wang, Bini; Zhang, Fuxin; Yang, Xingbin; Zhang, Youlin
Abstract: Zinc (Zn) is an essential micro-nutrient for humans, and Zn deficiency is of global concern. In addition to inherited and pathological Zn deficiencies, insufficient dietary intake is leading cause, especially in those consuming cereal grains as a stable food, in which Zn concentration and bioavailability are relatively low. To improve Zn levels in the human body, it is important to understand the accumulation and bioavailability of Zn in cereal grains. In recent years, knowledge on the molecular mechanisms underlying Zn uptake, transport, homeostasis, and deposition within cereal crops has been accumulating, paving the way for a more targeted approach to improving the nutrient status of crop plants. In this paper, we briefly review existing studies on the distribution and transport pathways of Zn in major small-grained cereals, using wheat as a case study. The findings confirm that Zn transport in plants is a complex physiological process mainly governed by Zn transporters and metal chelators. This work reviews studies on Zn uptake, transport, and deposition in wheat plants, summarizes the possible barriers impairing Zn deposition in wheat grains, and describes strategies for increasing Zn concentration in wheat grains.